Termotolerância de Metarhizium spp. e efeito de sua formulação sobre a virulência para Rhipicephalus microplus expostos à condições estressantes de temperatura e umidade - Muniz, Elen Regozino (2015)
Rhipicephalus microplus, known as tick of the cattle, cause great economic losses each year in Brazil. Entomopathogenic fungi stand out as an alternative to the exclusive control and indiscriminate use of the chemical. However, ambient temperature above the threshold considered optimal for these organisms can interfere with your biology, and compromise their development and effectiveness. In the present study evaluated biological parameters seven strains of Metarhizium spp. (IP1, IP34, IP46, IP60, IP119, IP125 and IP146) originated from the Central Brazil, incubated at 32 ± 0.5°C or 27 ± 1°C. In addition, the virulence was assessed for each strain of R. microplus engorged females. IP119, Metarhizium anisopliae s.s., was selected among the other isolates for virulence tests against R. microplus submitted with stressful temperature condition (32 ± 0.5°C) or low relative humidity (RH = 75%) to present considerable heat tolerance and virulence in the screening tests. Tests with conidia formulated in oil-water emulsion (liquid vaseline 5%), carboxymethylcellulose gel or emulgel 5% were conducted to evaluate the conidial thermotolerance when exposed to 45°C for 4 hours or 6 hours, and to test the efficacy of formulated to control engorged female R. microplus the stressful conditions of temperature (32°C) and low humidity (RH = 75%). It was concluded that a constant temperature of 32°C or exposure for a few hours at 45°C is stressful condition for the isolates. The conidia IP119 when bathed in liquid vaseline jelly were more tolerant of exposure to 45°C for 4 hours. IP119 was shown to be virulent for engorged female R. microplus, being the oil-water emulsion 5% of the most effective formulation.